2015
DOI: 10.1155/2015/513219
|View full text |Cite
|
Sign up to set email alerts
|

NT-proBNP as Early Marker of Subclinical Late Cardiotoxicity after Doxorubicin Therapy and Mediastinal Irradiation in Childhood Cancer Survivors

Abstract: Background. Childhood cancer survivors treated with anthracyclines and mediastinal irradiation are at risk for late onset cardiotoxicity. Aims of the Study. To assess the role of N-terminal pro-brain natriuretic peptide (NT-proBNP) and tissue Doppler imaging (TDI) as early predictors of late onset cardiotoxicity in asymptomatic survivors of childhood cancer treated with doxorubicin with or without mediastinal irradiation. Methods. A cross-sectional study on 58 asymptomatic survivors of childhood cancer who rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 44 publications
(52 reference statements)
3
18
0
3
Order By: Relevance
“…Cardiac biomarkers such as N‐terminal proBNP, cTnI and cardiac troponin T and CK‐MB have been used to assess cardiotoxicity . Among these, proBNP has shown promise as an early marker of late toxicity, and it also correlates with left ventricular systolic and diastolic function . Toxicity is dose‐ and time dependent, with more toxicity observed in patients receiving higher doses of anthracyclines .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac biomarkers such as N‐terminal proBNP, cTnI and cardiac troponin T and CK‐MB have been used to assess cardiotoxicity . Among these, proBNP has shown promise as an early marker of late toxicity, and it also correlates with left ventricular systolic and diastolic function . Toxicity is dose‐ and time dependent, with more toxicity observed in patients receiving higher doses of anthracyclines .…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, the utility of troponin in long-term surveillance of cancer survivors seems weak. However, brain natriuretic peptides appear to be potential early indicators of late cardiotoxicity during cancer survivorship as they have been associated with increased LV dimensions and echocardiographic features of systolic and diastolic dysfunction [ 39 41 , 56 , 57 , 64 , 65 ].…”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…A number of biomarkers, such as cardiac troponin T (6), fluorouracil (23) and circulating microRNAs (24) have been reported to have a predictive role in identifying AIC. Serum BNP elevation during chemotherapy has also been well investigated (13). The present study focused on monitoring the dynamic variation in serum BNP levels during anthracycline chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…multiple studies demonstrated that serum BNP may be an independent biomarker in detection of cardiotoxicity, however, relatively little known is about the predictive applicability of BNP in anthracycline-treated patients (9)(10)(11)(12)(13). Therefore, the aim of the present study was to assess the potential role of BNP detection in the early prediction of anthracycline-induced cardiotoxicity in patients with breast cancer.…”
Section: Bnp As a Marker For Early Prediction Of Anthracycline-inducementioning
confidence: 99%